2016
DOI: 10.1080/21623945.2015.1122855
|View full text |Cite
|
Sign up to set email alerts
|

The protein source determines the potential of high protein diets to attenuate obesity development in C57BL/6J mice

Abstract: The notion that the obesogenic potential of high fat diets in rodents is attenuated when the protein:carbohydrate ratio is increased is largely based on studies using casein or whey as the protein source. We fed C57BL/6J mice high fat-high protein diets using casein, soy, cod, beef, chicken or pork as protein sources. Casein stood out as the most efficient in preventing weight gain and accretion of adipose mass. By contrast, mice fed diets based on pork or chicken, and to a lesser extent mice fed cod or beef p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 57 publications
8
55
0
Order By: Relevance
“…However because the amount of protein administered is not considered as a HP-diet, it also does not causes the problems of health deterioration as reported recently [30]. But most important, it has been described that the type of protein could have different effects on body weight [31]. In this sense, AMA protein had the ability to maintain the CHO and TG at the same levels of Ctrl diets (Table 3) while SOY treatment produced a rise of CHO and TG levels and the only difference between the AMA and SOY protein isolates is their amino acid composition.…”
Section: Discussionmentioning
confidence: 99%
“…However because the amount of protein administered is not considered as a HP-diet, it also does not causes the problems of health deterioration as reported recently [30]. But most important, it has been described that the type of protein could have different effects on body weight [31]. In this sense, AMA protein had the ability to maintain the CHO and TG at the same levels of Ctrl diets (Table 3) while SOY treatment produced a rise of CHO and TG levels and the only difference between the AMA and SOY protein isolates is their amino acid composition.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent animal studies have found that a diet containing proteins from lean seafood tends to be less obesogenic than a regular Western diet containing proteins from meat such as chicken, pork, or beef. 30,65 Comparison of the gut microbiome of mice fed 2 different Western diets (with lean seafood vs lean meat) revealed significant differences in the abundance of microbial genes. 30 Marine protein sources tend to have moderate to high content of the branched-chain amino acids valine, leucine, and isoleucine.…”
Section: Possible Links Between Fish Proteins and Gut Microbiotamentioning
confidence: 99%
“…67 However, compared with proteins from fish, the milk proteins casein and whey have an even higher content of branched-chain amino acids, and casein has been shown to be more efficient than proteins from cod in preventing weight gain and an increase in adipose tissue in mice. 65 Fish proteins, the gut microbiota, and lipid status A randomized controlled crossover trial previously reporting on glucose and lipid metabolism in response to lean seafood consumption in 20 healthy human individuals 1,3 recently also reported on the effect of lean seafood and non-seafood consumption on fecal metabolites and the gut microbiome. 68 The authors observed a twofold increase in fecal trimethylamine excretion after the lean seafood intervention.…”
Section: Possible Links Between Fish Proteins and Gut Microbiotamentioning
confidence: 99%
“…In past decades, an unprecedented increase has been seen in metabolic syndromes including obesity, diabetes, hyperlipidemia, hyperinsulinemia, and cardiovascular disease ( Shang et al, 2017 ). Unfavorable patterns of food intake may cause dysfunctions in lipid metabolism and metabolic syndromes because it has been established that accumulation of lipid and triglycerides in liver consequently results in fatty liver disease, hepatic steatosis, and even diabetes ( Maeda et al, 2015 ; Liisberg et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%